Islamic Religious Education Model with Knowing-Doing-Meaning-Sensing-Being Approach to Realize Knowledge Integration - Sodikin Sodikin; Imaduddin Imaduddin; Zainal Abidin; Akhmad Sirojuddin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The transformative education of pesantren has become an idol among the community because it has advantages from scientific integration. This article aims to describe and find out the model of Islamic Religious Education with the Knowing-Doing-Meaning-Sensing-Being approach to Realize the Integration of Science. This article uses a type of qualitative research with a case study approach. The data collection technique is done by interview, observation, and documentation. At the same time, the data analysis technique uses the method of Miles and Huberman, namely by data reduction, display, and verification. This article shows that education teaches children to understand what must be done in everyday life. The formation of children's character with habituation is carried out in Islamic boarding schools. The education model carried out by MAN Al-Yasini is integrated, namely by strengthening the feeling of transformative education.